Impact of Using Excellence Management Models in the Customer Satisfaction of Brazilian Electricity Distributors - 10 Years of Studies - Andrade, M. A. P.; Rosa, A.; Alexandre Carrasco; M. Filomena Teodoro (IInternational Conference on Computational Science and its Applications - ICCSA, 2020)
In this work we evaluate the impact of the use of the model of excellence in Brazilian management by electricity distribution companies and their impact on customer satisfaction. It was evaluated 10 years of use of the model in groups of companies with different levels of implementation of the model MEG (users, indifferent, engaged and winning) using a statistical approach, firstly using descriptive statistics and by last applying the nonparametric kruskal-Wallis test. It is evidenced the existence of differences between the identified groups revealing the correct decision using the described model. We could attest the positive effects evidenced by the use of reference models of the electric energy sector, on a large scale, during the period analyzed. The results here obtained can be used, at least as guidance, by similar organizations or other industries.